A collimator design method for the tomographic gamma scanning system with a fan-shaped NaI(Tl) detector array. (April 2022) - Mu, Xiangfan; Shi, Rui; Luo, Geng; Tuo, Xianguo
Abstract: The detection speed of the tomographic gamma scanning (TGS) system with a detector array is faster than the single detector system. The NaI(Tl) detector is inexpensive and can work at room temperature, making it ideal for use in the TGS system with a fan-shaped detector array. The collimator of the TGS system is one of the critical elements to ensure the reconstructed image's quality. In addition to providing good detection efficiency of the detector while improving the system's spatial resolution, a proper collimator structure may also reduce cross-interference between segments. We propose a collimator design method for the TGS system with a fan-shaped NaI(Tl) detector array and combine it with the Monte Carlo method to optimize the collimator. We get the collimator aperture size and shape of the TGS system through the simulation results. Simultaneously, according to the detectors' equiangular sector arrangement limitation, we propose setting up a fan-shaped shield with adjustable depth and height at the detector collimator's front. The cross-interference between segments is effectively reduced without reducing the current segment's detection efficiency. The transmission image reconstruction shows that the collimator designed by this method can be used in the TGS system with the fan-shaped NaI(Tl) detector array. Highlights: The collimator of the TGS system with the fan-shaped NaI(Tl) detector array is optimized with the Monte Carlo method. The fan-shaped shield effectively reduces the cross-interference between segments. A TGS system with a fan-shaped NaI(Tl) detector array is adopted to reconstruct transmission tomography.